2022
DOI: 10.1155/2022/9902380
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis and Construction of a Prognostic Model after Percutaneous Coronary Intervention in Patients with Chronic Total Occlusion

Abstract: Background and Objective. Percutaneous coronary intervention (PCI) is expansively used in the treatment of chronic total occlusion (CTO), but there is a lack of effective means to predict the prognosis of CTO patients undergoing PCI. The aim of this study was to construct a risk model that could effectively predict disease progression after PCI treatment in patients with CTO and enrich the means of clinical prediction of prognosis. Methods. The clinical data of 82 patients with CTO who underwent PCI in Lianshu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…60 percent of patients in the current research presented with mass and calcifications; a lower frequency of mass lesions (55 percent) was found in the study of (13), which may be ascribed to the larger sample size of his study group. In the present investigation, three individuals had merely worrisome calcifications, whereas the remaining patient had architectural deformity.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…60 percent of patients in the current research presented with mass and calcifications; a lower frequency of mass lesions (55 percent) was found in the study of (13), which may be ascribed to the larger sample size of his study group. In the present investigation, three individuals had merely worrisome calcifications, whereas the remaining patient had architectural deformity.…”
Section: Discussioncontrasting
confidence: 62%
“…(17,2014,8,2007) In the ultrasound-guided biopsy investigation, the peak age incidence varied between forty and fifty years old. (13,14,2014) reported a mean age of 38 years and indicated that all research participants had mammographically dense breasts. Dense breast tissue is often linked with younger age and premenopausal status, and as age increases, the density of breast tissue diminishes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked the clinical profile of ACS patients at admission to prognosis, with age, cardiac insufficiency, and blood pressure clinically recognized as independent markers of poor prognosis following PCI in ACS patients (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%